COVID-19 as Force Majeure in Insurance Agreement - Padmo, Aditya; Joesoef, Iwan Erar (Faculty of Law, Mulawarman University, 2020)
Force majeure is an unexpected or unknown event which occur out of control that obstructs a party to fullfill the obligations in the agreement. This clause exempts the parties from the obligation to compensate either overall or partially for conducting default on contract. This research is normative legal research conducted by examining secondary, primary, and tertiary legal materials. As for research, conducted using conceptual approach and statute approach. The results show that COVID-19 is a relative force majeure. This condition affects the debtor’s economic ability to pay premiums to insurance companies every month. But according to article 1244 ICC the debtor must prove that the condition cannot be blamed on them. After it is proven article 1245 ICC can be applied which exempts the debtor from the obligation of compensation. In the face of COVID-19 as a force majeure insurance companies can implement an agreement restructuring policy in accordance with Financial Services Authority Regulations Number 14 of 2020. By implementing this policy insurance company can avoid the cancellation of the agreement due to force majeure.